Beyond Distribution: Analisis Dampak Pendayagunaan Zakat Produktif terhadap Keberlanjutan Usaha Mustahik Binaan LAZISMU Jawa Barat - Molly Mustikasari; Dadang Mulyana; Muhammad Ilham Maulana (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
Productive zakat distribution is an alternative for poverty reduction, but focusing solely on distribution does not have an impact on sustainable businesses. Mentoring is crucial but often neglected, given that zakat funds are prioritized specifically for beneficiaries (mustahik). High costs in the process make its implementation less than optimal. This research is crucial because productive zakat distribution enables beneficiaries to maintain their businesses. This study aims to analyze the implementation of the productive zakat program on business sustainability. The research method used was a qualitative approach using in-depth interviews with beneficiaries and program administrators. The results show that the productive zakat program has been running well in terms of aid distribution, indicated by easy access to capital. The program's effectiveness in improving business sustainability is still suboptimal, as evidenced by the unstable and fluctuating business conditions of beneficiaries. The need for standardized business mentoring is a solution for business sustainability, considering that mentoring is a process of increasing business capabilities that lead to business growth.